Fully-threaded cannulated screws versus partially-threaded cannulated screws for femoral neck fractures: a systematic review and meta-analysis - Mingwang Jia; Chenning Ding; Xin Zhao; Xing Han; Jiahui Zhang; Xiguang Sang (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Objective Femoral neck fractures (FNFs) are a common orthopedic type, and there are many treatment methods for it, and cannulated screw internal fixation is currently one of the main treatment methods. The choice of fully threaded cannulated screw (FCS) or partially threaded cannulated screw (PCS) remains controversial. Therefore, we performed this meta-analysis to evaluate the outcomes of FCS and PCS in the treatment of FNF. Methods Articles published before 29 April, 2024 were selected from PubMed, Embase, the Cochrane Library, and CNKI, using the PRISMA guidelines. Two independent reviewers searched and assessed the literature. The PICOS criteria were used to ensure that the included studies met the inclusion criteria. We used RevMan 5.3. Software to perform analysis. Results Compared with the PCS group, the FCS group had a lower femoral head necrosis rate (OR 0.60, 95% CI 0.37–0.98, P = 0.04), lower internal fixation failure rate (OR 0.37, 95% CI 0.22–0.62, P = 0.0002) and lower femoral neck shortening rate (OR 0.27, 95% CI 0.19–0.40, P < 0.00001). There was no statistically significant difference between the two groups in terms of the Harris hip score or nonunion rate. Conclusions The results of this meta-analysis revealed that compared with PCS, FCS had a lower incidence of postoperative complications and better postoperative outcomes in the treatment of FNF. Therefore, we believe that FCS may be a more effective treatment for FNF.